A Prospective, Randomized, Controlled Trial Comparing Radiographic and Clinical Outcomes between Stand-Alone Lateral Interbody Lumbar Fusion with either Silicate Calcium Phosphate or rh-BMP2 - Pimenta, Luiz; Marchi, Luis; Oliveira, Leonardo; Coutinho, Etevaldo; Amaral, Rodrigo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Object Iliac crest autograft has traditionally been considered the gold standard for lumbar spine fusion, though it is not without drawbacks related to harvesting site pain and other complications. Bone graft alternatives, such as recombinant human bone morphogenetic protein 2 (rh-BMP2), are now widely used but also have unique risk profiles and substantially increase costs. The purpose of the current study was to compare the efficacy of rh-BMP2 and synthetic silicate calcium phosphate (SiCaP) as bone graft substitutes on fusion rates and clinical outcomes in patients undergoing single-level lumbar stand-alone extreme lateral interbody fusion (XLIF).Methods A prospective, randomized, controlled, clinical, and radiographic study was performed at a single institution. Thirty patients with L4–L5 degenerative disc disease (DDD) were enrolled. Patients were randomized into one of two groups, 15 underwent lumbar single-level stand-alone XLIF using SiCaP, and 15 using rh-BMP2. Clinical and radiographic results were compared between the study groups. Pain (visual analogue scale) and disability (Oswestry disability index) were assessed preoperatively and at postoperative weeks 1 and 6 and postoperative months 3, 6, 12, 24, and 36. Radiographic evaluations were performed at 6, 12, 24, and 36 months. Neurological examinations and adverse events were recorded at each visit.Results No intraoperative complications were observed in either treatment group, and clinical outcomes were similarly improved between bone graft substitutes from baseline to 36 months postoperative. Complications were transient hip flexion weakness (13%), insufficient indirect decompression (7%), subsidence (17%), excessive bone formation (4%), and adjacent segment disease (14%). Complication rates between the groups were similar, though with slightly more instances of subsidence in the SiCaP group and higher rates of excessive bone formation and adjacent segment disease in the rh-BMP2 group. Rates of fusion at different time points were different between the groups, with the SiCaP patients progressing more slowly toward solid fusion. However, at 36 months, 100% of patients undergoing XLIF achieved solid fusion.Conclusions In stand-alone XLIF, SiCaP and rhBMP-2 bone graft substitutes both resulted in complete long-term fusion. rhBMP-2, however, seemed to result in more rapid early postoperative fusion, though with one instance of excessive bone formation in one patient that required subsequent surgical intervention.
Keywords: biologics; bone graft; lateral access; XLIF; bmp